THE POETICS OF WAR IN THE COLLECTION OF SHORT STORIES BY MARKO CHEREMSHYNA «SELO ZA VIINY» AND CONTEMPORARY UKRAINIAN SHORT STORIES - Liakh, Tetiana (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
Summary. The article deals with the poetics of war, defines genre specificity, outlines the national and existential discourse in the collection of short stories by Marko Cheremshyna «Selo za viyny» («Village during wartime») and in the short stories of modern Ukrainian authors (S. Zhadan, A. Chekh, K. Moskalets, etc.). Existential situations of human’s life during wartime are pain, fear, powerlessness, homelessness, as well as positive existential situations of hope, faith, and compassion. These situations are head in the works on the theme of war by Marko Cheremshyna and modern authors. A comparative analysis of Marko Cheremshyna collection «Selo za viyny» and contemporary Ukrainian short stories outlines further ways of researching short stories on the theme of war, the understanding of the poetics of short story genre.